The social importance of the migrants in the states development - Rodrigues, Carlos (2022)
The International Migration in the global and complex nowadays context need and must be continuously studied and understanding due the relevance of the mobility of millions of human beings around the world, as well as there is a basic need to promote different perspectives of this reality based on real data. Depending on the context of the Migrant State, life conditions or need to survive, in fact there are multiple reasons for the Migration and consequently the conditions provided to live and work. Due the Pandemic, since 2020 there were several changes of the International Migration due the restrictions to accept and integrate them, as the multiple motivation to migrate, however it was uninterrupted movement. In 2021 was globally registered 29 million of Migrants, but the real number it is higher due the illegal ones. From the international data and the facts, the Migrants social contribution to the States it ́s undoubtable: employment rates and inherent GDP growth; (2020: 73% -international migrants worldwide were between 20 -64 years old, compared to 57% for the total population”); demographic performance; the economic and financial evolution (decreasing or contributing to prevent poverty). Although most of the States have public policies to receive, protect and integrate Migrants, there is a serious need to develop a strategic education for their effective social importance, promoting a continuous evolution of the Political and Social behavior with these human beings and, in a special need and context, to promote a renew ethical and human International Public Opinion.